Kajian Frase dalam Novel Sang Pemimpi Karya Andrea Hirata - Azzahra, Anzalika; Fauziyah, Fauziyah; Fazillah, Nur; Nabila, Putri; Diana, Rahma; Zuyyina, Rifni (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to analyze the sentence structure and types of sentences found in Sang Pemimpi, a novel by Andrea Hirata. The research is grounded in the need to understand syntactic structures in literary texts as part of broader linguistic analysis. The central research question focuses on identifying the forms and classifications of sentences and phrases used in the novel. Employing a qualitative approach, the study utilizes descriptive analysis to examine data collected through reading and note-taking techniques. An observational method is applied to describe and interpret syntactic patterns found in the text. The findings reveal two key results: (1) based on sentence type, four categories were identified—isolated sentences, endocentric constructions, structured sentences, and syntactically correct sentences; and (2) based on core lexical categories, four phrase types were found—noun phrases, verb phrases, adjective phrases, and numeral phrases. These results indicate that Sang Pemimpi demonstrates a rich syntactic diversity, making it a valuable resource for linguistic and syntactic study within literary discourse.